Pelatihan Pemanfaatan Bioslurry di Desa Rejomulyo, Kecamatan Jati Agung, Lampung Selatan - Mareli Telaumbanua; Febryan Kusuma Wisnu; Siti Suharyatun; Agus Haryanto; Winda Rahmawati; Sri Waluyo (Education Language and Arts (ELA), 2022)
Biogas technology from floating drum-type cow dung made in Rejomulyo village, Jati Agung sub-district, South Lampung, can produce biogas for daily fuel. However, the residual waste or biogas dregs (sludge/bio-slurry) have not been utilized, only disposed of at a waste disposal site. This community service activity aims to increase the added value of biogas waste by utilizing sludge/bio-slurry for organic fertilizer in vegetable cultivation in yards and gardens. The activity was carried out using the extension method for making vegetable cultivation pilot units using sludge/bio-slurry. Furthermore, through Gapoktan and Agricultural Extension as companions, it can be developed in people's homes that have a biogas digester. The conclusion is that cow dung as waste from livestock business has been successfully converted into biogas and slurry. The success of this training is indicated by the high enthusiasm of the participants and the ongoing implementation of liquid fertilizer (bio-slurry).